Harmoni dalam keragaman: Membangun toleransi beragama di Indonesia - Laili, Farida Nur (Maliki Interdisciplinary Journal, 2026)
In today’s world, societies across the globe—especially in Indonesia—exhibit significant diversity in terms of culture, race, language, ethnicity, and religion. This diversity is inevitable, and its existence can lead to friction; however, eif handled with care and diligence, it is possible to prevent conflicts between different groups. This approach begins with fostering an understanding of what tolerance is, particularly religious tolerance. Building religious tolerance within society serves as the foundation for creating a happy and peaceful community. In fostering religious tolerance, there are inevitably challenges to overcome, such as intolerance and radicalism, stereotypes, prejudice, and other issues. Strategies that can be implemented include enhancing multicultural education, promoting interfaith dialogue, engaging religious leaders, and intensifying public awareness campaigns. To ensure that future generations can live together peacefully amidst diversity, practical and sustained measures must be implemented by the entire community.